2007
DOI: 10.1097/mop.0b013e32825b0788
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented lesions in children: when to worry

Abstract: Clinical and molecular investigations have helped to better understand the characteristics of melanocytic nevi and define pathways of melanocytic tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 96 publications
0
27
1
2
Order By: Relevance
“…This finding is concordant with the medical literature, in fact most Spitz nevi are known to occur on the face and lower extremities. 6 There was no positivity for CD133 in all of the Spitz nevus cases. Moreover, all of the Spitz nevi behaved in a benign manner and did not recur.…”
Section: Immunohistochemical Stainingmentioning
confidence: 86%
See 1 more Smart Citation
“…This finding is concordant with the medical literature, in fact most Spitz nevi are known to occur on the face and lower extremities. 6 There was no positivity for CD133 in all of the Spitz nevus cases. Moreover, all of the Spitz nevi behaved in a benign manner and did not recur.…”
Section: Immunohistochemical Stainingmentioning
confidence: 86%
“…5 Spitz nevus, previously named benign juvenile melanoma by Sophie Spitz, is a benign acquired proliferation of melanocytes, commonly presenting in childhood with histopathological features that sometimes overlap with those of malignant melanoma. 6,7 Klein et al 4 observed significant increases in the expression of the stem cell markers CD133, CD166 and nestin in primary and metastatic melanoma in comparison with their expression in banal nevi.…”
mentioning
confidence: 99%
“…28,29 Esta investigação sistematiza, a partir das observações dos pacientes no IPPMG e dos dados de literatura, elementos que podem auxiliar dermatologistas e pediatras no diagnóstico e acompanhamento dos portadores de NMC. …”
Section: Conclusãounclassified
“…Epitheliod BN are a histologic subtype of nevi that are associated with the Carney complex in children, encompassing a triad of cardiac myxomas, skin hyperpigmentation and endocrine overactivity [54]. As a general rule, BN are benign in children; however, on exceedingly rare ocassions, a large, evolving, blue-black plaque may represent a primary or metastatic melanoma ('malignant blue nevus') [55][56][57].…”
Section: Blue Nevimentioning
confidence: 99%